STRATEGIC HUMAN RESOURCES MANAGEMENT IN SCHOOLS talent centered education leadership. - Tran, Henry (Professor of education finance); Kelley, Carolyn ([S.l.] : ROUTLEDGE, 2024)
Strategic Human Resources Management in Schools provides a new approach to human resources management, grounded in the perspectives of cutting-edge practice, research, and theory. Traditional human resource (HR) practices in education have operated in an isolated and reactionary manner; this book explores an updated version of personnel administration that links strategic human resources to organizational goals, educational mission, educator well-being, and student success. Coverage includes exemplar strategic HR practices from progressive organizations and leading companies, discussion of tricky issues like discrimination and implicit bias, and developmental and humanistic support of teachers as well as support staff, including paraprofessionals, food service workers, and bus drivers. The Talent-Centered Education Leadership (TCEL) model presented in this book explores how educational leaders can create a nurturing and inclusive workplace for all educational staff, which is ultimately critical for improvement in student learning and strengthening recruitment and retention of a quality education workforce. Designed for aspiring leaders, this volume is grounded in the Professional Standards for Educational Leaders (PSEL) and National Educational Leadership Preparation (NELP) Building and District Level standards and is full of rich pedagogical features including cases, warning boxes to explore areas particularly thorny to navigate, questions for discussion, and various learning activities.
Keywords: School personnel management; School management and organization; EDUCATION / Leadership